ROFIL MOTIVASI BELAJAR PESERTA DIDIK PINDAHAN DI KELAS XII SMA PERTIWI 2 PADANG - Wati, Hasmila - (Bimbingan dan Konseling, 2014)
This research was back grounded thereâs still transferred student who is lack of motivation in studying, there got lazy, out from the class when are time changing and also lack of spirit in making the tasks. The purpose of this research is to know that : 1) the internal studying motivation profiles of transferred student, 2) the external studying motivation profile of transferred student. This research is descriptive and quantitative research. The population of this research is the transferred student class XII from 20 student. The sampling technique total sampling. Instrumen which are used to collect the data is questionnaire. Using data a analyeie, itâs used criterium sturgess formula and percentage analysis technique. The result of this result stated that: 1) the internal studying motivation profile of transferred student categorized high enough, 2) the external studying motivation profile of transferred student categorized high enough. This research recommended to the transferred student to increase studying motivation.